Unveiling the needs of students who stutter in the language skills - a study on anxiety and stuttering in EFL learning. Issue 2 (15th March 2019) - García-Pastor, María Dolores; Miller, Ronan
ABSTRACT: The aim of this study is to discuss the needs of learners who stutter (LWS) in the skills of speaking, listening, reading, and writing in English as a foreign language (EFL) learning based on their levels of anxiety, and their experiences as individuals who stutter in the process of learning this language. To this end, the anxiety of these students (n = 16) in the foreign language was measured using the Foreign language classroom anxiety scale (FLCAS), and the Specific language skills anxiety scale (SLSAS), whilst their experiences were elicited through semi-structured interviews. Their foreign language anxiety (FLA) levels were then compared to those obtained from a control group of non-stuttering learners (n = 16), and interview content was scrutinised mainly using Interpretive Phenomenological Analysis (IPA). LWS scored significantly higher in FLA and speaking anxiety than the control group; however, no significant differences were found between both groups in other language skills. Findings from the qualitative study also indicated that reading aloud was highly problematic for these learners. Suggestions to attenuate anxiety in LWS are offered to educators.